2016
DOI: 10.1016/j.jece.2015.09.018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chemical composition on the leaching behaviour of electric arc furnace (EAF) carbon steel slag during a standard leaching test

Abstract: The electric arc furnace (EAF) slag could be exploited in several fields of application, such as land filling, road constructions and concrete production. However, their use is limited by the presence of polluting chemical elements (chromium (Cr), barium (Ba), Vanadium(V), etc.) that can be dangerous to humans and the environment. Thus, chemical and structural stability is a fundamental requirement, especially when the slag may come in contact with water. Therefore, the interaction between slag and water is ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 36 publications
6
32
0
Order By: Relevance
“…Logically, only minerals that can contain Cr can leach Cr. There are four major ferrous EAF slag minerals that usually contain Cr: spinels (AB 2 O 4 ), merwinite (Ca 3 MgSi 2 O 8 ), brownmillerite (Ca 2 (Al,Fe) 2 O 5 ), and magnesiowüstite (MeO) . Depending on which elements the spinels consist of they can either stable or unstable Spinels become more soluble as the calcium content increases .…”
Section: Introductionmentioning
confidence: 99%
“…Logically, only minerals that can contain Cr can leach Cr. There are four major ferrous EAF slag minerals that usually contain Cr: spinels (AB 2 O 4 ), merwinite (Ca 3 MgSi 2 O 8 ), brownmillerite (Ca 2 (Al,Fe) 2 O 5 ), and magnesiowüstite (MeO) . Depending on which elements the spinels consist of they can either stable or unstable Spinels become more soluble as the calcium content increases .…”
Section: Introductionmentioning
confidence: 99%
“…By the correct addition, it is possible to change the chemical composition of a slag from the larnite stability field to the gehlenite-kirschsteinite stability field. Regarding the slag samples under examination, it seems that the stabilization treatment had a higher efficacy for the pot-tapped slag, as the A and B group samples fell exactly in the green areas of the ternary diagrams after the treatment [10]. On the contrary, the final chemical composition of the pit-tapped slag (C and D group samples) resulted far from the safety areas, even if the stabilizer amount injected was theoretically enough to move the slag to the safe chemical composition.…”
Section: Chemical Crystallographic and Microstructural Characterizamentioning
confidence: 99%
“…An alternative stabilizer of quartz is alumina, which causes the formation of the stable dicalcium aluminosilicate (or gehlenite) complex [9]. The presence of alumina reduces slag basicity and moves the system out of the dicalcium silicate (or larnite) stable region on the CaO-SiO 2 -Al 2 O 3 phase diagram [10]. Actually, alumina requirement depended on the binary basicity index (CaO/SiO 2 ) of the slag.…”
Section: Introductionmentioning
confidence: 99%
“…Despite studies highlighting the mineralogical variation between ISM facilities, 14) the typical reported information is limited to the slag source (e.g., BF, BOF, EAF) and the elemental composition as simple oxides. Work from the silicate rock-based CO 2 mineralization field has shown that the ostensibly similar Mg 2 SiO 4 and CaSiO 3 differ in CO 2 mineralization depth by ~4 orders of magnitude (≤40 nm 16) and ≥ 125 μm, 17) respectively), despite comparable thermodynamic driving forces (ΔG r = − 34.7 kJ/mol and − 39.5 kJ/mol, respectively) and dissolution rates.…”
Section: Mineralogy and Crystallinitymentioning
confidence: 99%